Medication-Related Problems and Interventions Identified and Addressed by Pharmacists Conducting Enhanced Medication Therapy Management Services - Laura E. Knockel; Yury Kim; Kelly Kent; William R. Doucette (MDPI AG, 2022)
Pharmacists identify, resolve, and document medication-related problems (MRPs) in community pharmacies. Enhanced medication therapy management (eMTM) targets specific situations, such as high-risk medications, while continuous medication monitoring (CoMM) occurs for every patient and is integrated into the dispensing process. This study describes types and frequencies of MRPs and interventions for health plan-directed eMTM and pharmacist-identified CoMM for a cohort of Medicare Part D patients. Pharmacy dispensing and clinical records from one independent community pharmacy in the Midwest were reviewed for patients eligible for eMTM in 2019. Data were coded for medication-related problems and interventions; descriptive statistics were calculated. Forty-seven patients were included in the study, resulting in 439 health plan-directed and 775 pharmacist-identified MRPs and corresponding interventions for a total of 1214 over 12 months. The average age of the patients was 77; they received an average of about 14 medications dispensed over 25 dates. Nonadherence was the most common MRP overall, as well as for the two categories separately. Patient Counseling and Lab Values Needed MRPs were found more often by pharmacists. Continue to Monitor was the most common intervention flagged overall. Medication Discontinued was found more often in health plan-directed interventions; Patient Counseling occurred more frequently in pharmacist-identified interventions. Using pharmacists to identify MRPs can complement health plan-driven eMTM, which can provide more complete medication management. Future work is needed to determine if this approach is reproducible in other pharmacies.